University and entrepreneurship, contributions for the professional training of entrepreneurs - Alvarado Muñoz, Oscar; Rivera Martínez, Wilfred (Cuadernos de Administración, 2011)
This research article shows the results of a project developed inside the programs leaded by the Faculty of Administration, Accounting and Economics at the Corporación Universitaria Autónoma del Cauca; the main objective is to establish basic guidelines to design a curriculum that articulates the entrepreneurial activity as a training area and the economic and social context of the Department of Cauca. The research is exploratory; it has a quantitative approach to identify and to characterize the entrepreneurial activity at the faculty, as predominantly economic categories. To achieve this goal, it was used a structured survey format implemented in 90% of students in the faculty. Besides, it was collected and analyzed information from the documents of territorial planning exercises conducted in the department of Cauca to identify the variables of the socio - economic context. The research results indicate a divorce between the characteristics of entrepreneurship in the Faculty and the main economic sectors in Cauca, so that the curriculum model proposes a series of spaces and strategies to facilitate a dialogue between university and the regional context and an approach of students to the realities and development needs of Cauca.